MAKNA SIMBOLIK TRADISI BERBALAS PANTUN PADA PERKAWINAN ADAT MELAYU LANGKAT - Fitri Yani,; Elly Prihasti Wuriyani,; Rosmawaty Harahap, (JOEL: Journal of Educational and Language Research, 2022)
This study aims to describe the traditions at Malay weddings that are often said to be signaled, reluctant to be direct, but always say something by using parables and figuratively indirectly (using rhymes). The Symbolic Meaning of the Langkat Malay Traditional Marriage Procession (A Research on Symbols Containing Meaning at the Face-to-Face Rice Dinner in the Langkat Malay Traditional Wedding Ceremony Reception is a habit, in fact it almost becomes a custom. It is as if the Malays often tell people to think more deeply by using a few words to find their own interpretation. Pantun is part of the nature of Malay people's life, which of course can be used as learning. Even the rhyme itself is always associated with the vast nature. The philosophy of the Malays views nature as mirror of human life. They read nature to understand the existing situation as expressed in the proverb Alam Terbentang Become Guru, so that in the rhyme in the first line there are elements of nature and the next line is put forward the truth. One of the traditional ceremonies and traditions that are full of with the expression is a traditional Malay wedding ceremony This very important ceremony is full of symbols and meanings, both in the form of ceremonial fittings and the expressions used. In this ceremony, many parts are filled with expressions so that the ceremony makes this traditional ceremony feel more sacred, thick, dignified and solemn.